ANALISIS PROSEDUR DAN TEKNIK THAI MASSAGE DALAM PELAYANAN BODY SPA PROFESIONAL - Alya Salsabila; Wisri Ardihta Manda Putri; Indah Regina; Syahrani Putri Alya; Syifa Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Thai Massage is one of the traditional therapies widely applied in professional body spa services due to its physical and psychological benefits. This study aims to analyze the procedures and techniques of Thai Massage in professional body spa services through a descriptive literature review approach. The research employed a qualitative method with a literature review design. Data were obtained from scientific journals, academic publications, and relevant references discussing Thai Massage, spa services, service quality, therapist professionalism, and customer satisfaction. The collected data were analyzed using content analysis techniques. The findings indicate that Thai Massage combines pressure, stretching, and body manipulation techniques performed through four main positions, namely supine, prone, side-lying, and seated positions. These techniques contribute to improving flexibility, reducing muscle tension, enhancing comfort, and providing relaxation. In addition, the quality of Thai Massage services is influenced by systematic service procedures, therapist professionalism, effective communication, customer privacy, sanitation practices, and service safety standards. Customer satisfaction in spa services is also strongly related to service quality and therapist competence. Therefore, mastery of Thai Massage techniques, implementation of professional ethics, and understanding of service safety procedures are essential factors in supporting professional body spa services that are safe, effective, and customer-oriented.Keywords: Thai Massage, professional body spa, spa services, therapist professionalism, wellness therapy.